2009
DOI: 10.3791/1394
|View full text |Cite
|
Sign up to set email alerts
|

Generating Chimeric Zebrafish Embryos by Transplantation

Abstract: One of the most powerful tools used to gain insight into complex developmental processes is the analysis of chimeric embryos. A chimera is defined as an organism that contains cells from more than one animal; mosaics are one type of chimera in which cells from more than one genotype are mixed, usually wild-type and mutant. In the zebrafish, chimeras can be readily made by transplantation of cells from a donor embryo into a host embryo at the appropriate embryonic stage. Labeled donor cells are generated by inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 12 publications
0
53
0
Order By: Relevance
“…Cell transplantations were carried out at the blastula stage as described previously (Kemp et al, 2009). Donor embryos [Tg(-4.9sox10:EGFP)] were injected with 1 nl of 3% Texas Red-conjugated Dextran (Life Technologies) at the one-cell stage.…”
Section: Cell Transplantationsmentioning
confidence: 99%
“…Cell transplantations were carried out at the blastula stage as described previously (Kemp et al, 2009). Donor embryos [Tg(-4.9sox10:EGFP)] were injected with 1 nl of 3% Texas Red-conjugated Dextran (Life Technologies) at the one-cell stage.…”
Section: Cell Transplantationsmentioning
confidence: 99%
“…For imaging, approximately 100 embryos were moved into an agarose-coated Ø 9 cm Petri dish with approximately 1 mm long, 1 mm wide, and 0.7 mm deep wells. Those wells were generated by a custom-made plastic mold similar to the one used by Kemp et al 14 The embryos for imaging in the well plates were replaced at least once a day. Embryos were cultured and imaged at 27.3°C.…”
Section: Embryo Culturementioning
confidence: 99%
“…42,43 Creation of zebrafish chimeras has been used to study the cell-intrinsic functions of cloche and bloodless genes in HSPC proliferation, survival, and differentiation. 26,27,44 Here, we demonstrated that transplanted cdh5-silenced blastula cells differentiate into red cells in WT zebrafish embryos.…”
Section: Discussionmentioning
confidence: 99%